Heterogeneous Fenton Degradation of Batik Wastewater using Natural Pyrite - Irawaty, Wenny; Yuliana, Maria; Wijaya, Christian J.; Retnoningtyas, Ery S.; Lourentius, Suratno; Puspitasari, Nathania; Hamidah, Umi (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2023)
Heterogeneous Fenton processes with solid natural pyrite catalyst have gained attention for wastewater treatment. The improvement of degradation efficiency of natural pyrite is specific and therefore, it is still a challenging issue. This study was aimed to investigate the performance of Indonesian natural pyrite, without any purification, to treat the real wastewater obtained from batik home industry. To address this issue, several experiment variables such as pre-reaction between pyrite and hydrogen peroxide, hydrogen peroxide concentration, and pH were investigated. COD removal has been found to increase in a slightly acid condition (4.5 to 5.65) and inhibited at pHs of 8 and above (10). The results showed the presence of hydrogen peroxide was indeed greatly influence the wastewater degradation and the solution pH did not significantly change the wastewater degradation in the range of 3 and less than 8. Moreover, the pre-reaction period was found as the important part to initiate the degradation process. The optimum degradation efficiency was obtained by providing the pre-reaction time of 20 min with the addition of 326 mmol/L of H2O2 in the system and the mixture was reacted for 30 min at room temperature and real wastewater pH. Based on results observed in this study, it can be concluded that the batik wastewater can be degraded by natural pyrite up to 84% under reaction conditions studied. This finding offers great opportunity to further investigate and develop the heterogeneous Fenton process for real applications in industry.